1998
DOI: 10.1007/s002340050608
|View full text |Cite
|
Sign up to set email alerts
|

MRI in primary intraspinal extradural hydatid disease: case report

Abstract: A rare case of pathologically proven primary intraspinal extradural hydatid disease of the thoracic region with spinal cord compression is reported. The diagnosis was established preoperatively on the basis of the MRI findings. The patient underwent surgery and recovered completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…6,16,27,30 Berk et al 30 reviewed MRI characteristics of the lesions and concluded that they had a unique appearance: A sausage-like shape with two dome shaped ends, thin and regular walls and no septation or debris in the lumen. The lesions are occasionally spherical.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…6,16,27,30 Berk et al 30 reviewed MRI characteristics of the lesions and concluded that they had a unique appearance: A sausage-like shape with two dome shaped ends, thin and regular walls and no septation or debris in the lumen. The lesions are occasionally spherical.…”
Section: Diagnosismentioning
confidence: 99%
“…Signal characteristics of the cyst content are usually similar to that of CSF. 27,30,31 On T1W images the cyst wall appears iso-or slightly more hypo-intense than the cyst content and enhances slightly after contrast injection. T2W images demonstrate a low intensity rim which correlates to the pathological ®ndings of reactive ®brosis and degeneration surrounding the parasitic membrane.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…1 A, Fig. 2A,B Postoperative MR image showing that the hydatid cyst was totally removed 12 cases of primary extradural hydatid cysts, including ours [2,3,4,5,7,10,14,15,16,18]. In reports originating from a period prior to computed tomography (CT) and MRI, the possibility of the existence of a single extradural hydatid cyst or of soft tissue involvement without bony origin was viewed with scepticism [13,19].…”
Section: Case Reportmentioning
confidence: 99%